Creating futures in science : a scenario-building workshop for early stage career female researchers for use by institutions.: a scenario-building workshop for early stage career female researchers for use by institutions. ([2015?]) - Portia (Organization : Great Britain),; Fraunhofer-Gesellschaft,; Universiṭat Tel-Aviv,
No abstract available